Study on Cross-wind Response of Single Steel Pipe Lightning Rod High Flexible Structure - Jinfeng JIAO; Yalan SU; Jie DENG; Xingqiang FU; Pengcheng CHEN (Taiyuan Ligong Daxue xuebao, 2023)
For single steel pipe lightning rod structure that has a circular cross section and low fundamental frequency, wind vibration phenomenon is easy to occur in the operation process. The two-way fluid-structure coupling method was used to conduct three-dimensional numerical wind tunnel simulation, and the mechanical properties and wind vibration response of steel pipe lightning rod structure under seven wind speeds were discussed. The outcomes were and compared with current national standard provisions. The analysis results show that the maximum transverse wind pressure on both sides of the lightning rod structure is 1.03 kPa under typical wind speed, which is 1.72 times the downwind wind pressure, and the abrupt change of wind pressure is significant at the connection of steel pipe in different sections. When the wind speed is greater than 10 m/s, the transverse wind pressure of the lightning rod structure is greater than the standard wind load value provided by the specification, the difference between the two is 42%, and the displacement of the top of the structure is 30.6%. When the wind speed is greater than 20 m/s, the transverse vibration frequency of the lightning rod structure is close to the high-order natural vibration frequency of the lightning rod structure, and the lightning rod structure is prone to produce high-order bending vibration, which has safety risks.